Secrecy Rate Adaptation Method of Sensor Nodes Based on Evolutionary Game - Shigen Shen; Longjun Huang; Angyan Tu; Hongjie Li; Risheng Han; Qiying Cao (Dianxin kexue)
By developing the classical wire-tap channel, an approach was proposed to compute the secrecy rate between a sensor node and its responsible cluster head in the clustered wireless sensor network. A non-cooperative secrecy rate game model was formulated to reflect on the interaction relationship between sensor nodes. Using evolutionary game theory, a selection scheme in which a power level can be adaptively selected by a sensor node was developed. Moreover, a corresponding algorithm of secrecy rate adaptation was proposed. Numerical experiments show that the proposed algorithm adaptively adjusts the secrecy rate of the sensor node. Therefore, a novel method to guarantee the confidentiality of wireless sensor network data was provided.